Periodicals, the Empire and the City in Victorian Culture - Korte, Barbara (The Grove - Working Papers on English Studies, 2025)
This contribution investigates the representation of cities of the British Empire in Victorian periodicals, a mass medium in the second half of the 19th century. Articles on all aspects of Empire were then a staple of the British periodical press. They increased their readers’ knowledge about the Empire and imbued them with imperial ideology. This is prominent in depictions of cities and their function as nodes in transport and communication networks, centres of trade, seats of government, administrative and educational institutions, contact zones as well as the demonstration of imperial power. The article focuses on the Indian cities Calcutta (now Kolkata), Delhi and Bombay (now Mumbai) and how they were related to the continuation of British rule through temporal categories such as progress, backwardness and tradition.